The Role of Digital Marketing Strategy on Patient Loyalty with Hospital Service as a Moderator in Regional Public Hospitals Across Greater Bandung - Maulana Sangsaka Nugraha; Putri Naira Radhita; Yen Efawati (SEAN Institute, 2026)
This study aims to analyze the influence of digital marketing strategy on patient loyalty, with hospital service as a moderating variable in Regional Public Hospitals across Greater Bandung. This study employs a quantitative approach using descriptive-verificative methods. The research sample consisted of 100 hospital patient respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using PLS-SEM through outer model testing, inner model testing, and bootstrapping. The results show that digital marketing strategy has a significant effect on patient loyalty, with a T-statistic value of 2.680 and a p-value of 0.049. Hospital service is also proven to strengthen the influence of digital marketing strategy on patient loyalty, with a T-statistic value of 2.706 and a p-value of 0.048. The R-Square value of 0.512 indicates that the model is able to explain patient loyalty by 51.2%. These findings emphasize the importance of alignment between digital information and the actual quality of hospital services.